ANALISIS KINERJA DAN KEBUTUHAN FASILITAS PELABUHAN PENYEBERANGAN PADANGBAI - Parahita, Nanda Angga; Suthanaya, Putu Alit; Wedagama, Dewa Made Priyantha (JURNAL SPEKTRAN; Vol 9 No 2 (2021)DO - 10.24843/SPEKTRAN.2021.v09.i02.p01, 2021)
In 2019 there are indication of decresed performance of Padangbai Port which can be seen from the long vehicles queues. Decline in performance is due to the high volume of vehicles unsuitable availability of facilities and infrastructure. This condition is exacerbated by the use of Padangbai Port to also serve the crossing to Nusa Penida. Damage to the pier or bad weather can also be the cause of reduced port performance. As an evaluation of the problems in 2019 and the impact of the Covid-19 pandemic in 2020, an analysis of operational performance evaluation is needed. To get ideal operational performance in the future, an analysis of the needs of ships, docks and ideal facility space is needed. The analysis is based on the prediction of the volume of passengers and vehicles by taking calculation from effect of the opening of the Banyuwangi - Lembar crossing route, which operates from 2021. In this study, the analysis of operational performance ata Port Padangbai in serving route Padangbai – Lembar was based on the Regulation of DJPL No. HK/103/2/2DJPL-17. The prediction of passenger and vehicle volume is carried out using 4 methods whics is growth factors based on GRDP, based on population growth, based on vehicle growth and regression analysis. From the 4 prediction methods, a representative prediction result will be selected. The calculation of ideal number of ship is based on the load factor and the calculation of the ideal dock is based on the ideal BOR value. The method of calculating the ideal facility space based on KepMen Perhubungan No. KM 52 Tahun 2004. The result show that the performance level of Port padangbai in 2020 is waiting time 13 minutes, approach time 19 minutes, ET/BT 63,42%, BOR in 2020 49% and BOR in 2019 85,74%. Prediction result of passanger and vehicle volume did not show a significant increase in the future. Result of the calculation ideal number of vessels are in 2019 26 units, 2020 19 units, 2025, 22 units, 2030 26 units, and 2040 30 units vessel. The ideal number of dock based on the calculation result show in 2019 ideally there are 3 docks, from 2020 to 2030, ideally there are 2 docks and in 2040 ideally there are 3 docks. The ideal facilty space calculation obtained the land side existing facility space is still adequate for 2019, but the availability of parking areas for crossing vehicles is prone to shortages. Meanwhile, the availability of land side facilities is currently still adequate for 2020 to 2040. The availability of water side facilities is not sufficient enough from 2019 to 2040.